2018
DOI: 10.1039/c8ra01490f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of HKUST-1 and zeolite beta composites for deep desulfurization of model gasoline

Abstract: Zeolite beta microspheres@nanosized HKUST-1 and micro-octahedron-shaped HKUST-1@nanosized zeolite beta composites were synthesized to remove thiophene from model oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…While the weight loss of P (BVS‐SO 3 H) is nearly double of that of the other two samples which reflected that the hydrophilic property of P (BVS‐SO 3 H) is much better ascribed to the acidification step of sulfuric acid. The disintegration of acidic groups is corresponding to the second stage, P (BVS‐SO 3 Na) shows a minor advantage of thermal stability than P (BVS‐SO 3 H) and P (BVS‐SO 3 H)‐SO 3 CF 3 . Apparently, the catalyst is stable enough before 300 °C.…”
Section: Resultsmentioning
confidence: 99%
“…While the weight loss of P (BVS‐SO 3 H) is nearly double of that of the other two samples which reflected that the hydrophilic property of P (BVS‐SO 3 H) is much better ascribed to the acidification step of sulfuric acid. The disintegration of acidic groups is corresponding to the second stage, P (BVS‐SO 3 Na) shows a minor advantage of thermal stability than P (BVS‐SO 3 H) and P (BVS‐SO 3 H)‐SO 3 CF 3 . Apparently, the catalyst is stable enough before 300 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Liang and co-workers synthesized two different Cu-BTC/BEA composites for ADS testing . The first adsorbent was composed of BEA @Cu-BTC nanoparticles (HKMB) and the second adsorbent was composed of micro-octahedron-shaped Cu-BTC@BEA nanoparticles (HKNB).…”
Section: Zeolitesmentioning
confidence: 99%
“…Liang and coworkers synthesized two different Cu-BTC/BEA composites for ADS testing. 145 The first adsorbent was composed of BEA @Cu-BTC nanoparticles (HKMB) and the second adsorbent was composed of micro-octahedron-shaped Cu-BTC@BEA nanoparticles (HKNB). For the HKNB, the BEA nanoparticles were found to have a diameter of 300 nm and were welldispersed and coated on the Cu-BTC to form a core−shell structure.…”
Section: Zeolitesmentioning
confidence: 99%
“…A very few studies have been reported that used composites to remove sulfur compounds . It has generally been reported that improvement in activity when composites are used is usually a result of the following: (i) enhancement of the volume of the composites; (ii) formation of an appropriate pore structure for the adsorption of a particular adsorbate; , and (iii) synergistic effects on the edge sites of metal species. …”
Section: Introductionmentioning
confidence: 99%